Use of enzyme-linked immunosorbent assay and dipstick assay for detection of Strongyloides stercoralis infection in humans. - Van Doorn, H; Koelewijn, R; Hofwegen, H; Gilis, H; Wetsteyn, J; Wismans, P; Sarfati, C; Vervoort, T; van Gool, T (2007)
A homemade enzyme-linked immunosorbent assay (ELISA) (Academic Medical Center ELISA [AMC-ELISA]) and a dipstick assay for the detection of anti-Strongyloides stercoralis antibodies in serum were developed and evaluated together with two commercially available ELISAs (IVD-ELISA [IVD Research, Inc.] and Bordier-ELISA [Bordier Affinity Products SA]) for their use in the serodiagnosis of imported strongyloidiasis. Both commercially available ELISAs have not been evaluated previously. The sensitivities of the assays were evaluated using sera from 90 patients with parasitologically proven intestinal strongyloidiasis and from 9 patients with clinical larva currens. The sensitivities of the AMC-ELISA, dipstick assay, IVD-ELISA, and Bordier-ELISA were 93, 91, 89, and 83%, respectively, for intestinal strongyloidiasis. In all tests, eight of nine sera from patients with larva currens were positive. The specificity was assessed using a large serum bank of 220 sera from patients with various parasitic, bacterial, viral, and fungal infectious diseases; sera containing autoimmune antibodies; and sera from healthy blood donors. The specificities of AMC-ELISA, dipstick assay, IVD-ELISA, and Bordier-ELISA were 95.0, 97.7, 97.2, and 97.2%, respectively. Our data suggest that all four assays are sensitive and specific tests for the diagnosis of both intestinal and cutaneous strongyloidiasis.